Rhetoric Effects of Vocative Particle (Yaa) [O] in Al-Mutanabbis’ Poetry: A Stylistic Study - Kadir Mugair, Sarab; Jalal Abbas, Aswan; Jasim Al-Hilu, Mazin (International Journal of Psychosocial Rehabilitation, 2020)
The study presents the linguistic issue about the emergence of the vocative particle (yaa) and its rhetorical effects in Al-Mutanabbi’s poetry. The study indicates a perspective on grammatical structure towards this phenomenon and afterward its implications that are identified with the context in which it is introduced, realizing that rhetoric neither originates from a solitary sentence, extricated from the content where it shows up, nor the outside impacts encompassing it. There are additionally numerous patterns of vocative particle (yaa) [O] that showed up in Al-Mutanabi’s poetry; these patterns are the caller of proper or singular noun, the caller of intended noun, and the caller of unintended noun. Examining this phenomenon doesn’t intend to advocate it, yet it is a feature that is deserving of being studied. Besides its normal uses, this study aims to show how the vocative particle (yaa) [O] is used for rhetorical purposes in Al-Mutanabbi’s poetry. However, the study is going to follow certain notions taken from scholars such as Larson (2014) and Hill (2017) as its model.